PANDANGAN POSITIF DAN NEGATIF TERHADAP KARYA-KARYA ANTROPOLOGI ISLAM DI INDONESIA - Fajarini, Ulfah (Universitas Islam Negeri Raden Intan Lampung, 2014)
POSITIVE AND NEGATIVE OUTLOOKS IN THE WORKS OF ANTHROPOLOGY OF ISLAM IN INDONESIA: This article compares the works of Western and Indonesian anthropologists who studied Islam in Indonesia as well as to uncover positive and negative western anthropologists insights reflected in their works.To parse this phenomenon, the author examines several academic works of a number anthropologists such as: Clifford Geertz’s, a pioneer in understanding and explaining the phenomenon of Muslims in Indonesia; Anthony Reid’s, the founder of the concept of “nationalist orthodoxy”; Robert Jay’s, who reveal the influence of religion on political schism between the Santri (devout Muslim or Islamist) and the Abangan (less devout Muslims); along with some other works such as: Andrew Beatty’s, John R. Bowen’s, Robert W. Hefner’s, JL Peacock’s, Martin van Bruinessen’s, and Mark R. Woodward’s. Aside from that, the author also tries to uncover the role of Indonesian Islamic anthropologists pioneered by researchers from the Research Center for Religious Life of the Ministry of Religious Affairs.